Two new sympatric Knipowitschia species (Teleostei: Gobiidae) from an eastern Mediterranean coastal lake—examples of different dispersal patterns? - Ahnelt, Harald (Zootaxa, 2011)
Two new species of the genus Knipowitschia, Knipowitschia byblisia sp. nov. and Knipowitschia caunosi sp. nov., are described from the coastal Lake Köycegiz, southwest Turkey. Knipowitschia byblisia sp.nov. is placed in a group of species with reduced cephalic lateral-line canals and reduced squamation. This species is characterized by the presence of axillary and caudal peduncular patches of scales, by a distinct reduced head canal system with only the postorbital section of the supraorbital canal developed and with longitudinal and transversal rows of free neuromasts in the interorbit. Knipowitschia caunosi sp. nov. is placed in a group of species with a fairly complete head canal system and with scales continuously extending along lateral midline from the axilla to the caudal peduncle. This species is characterized by long transverse rows of free neuromasts on the nape and on the cheek, by a characteristic pattern of the preorbital series of free neuromasts with the anteriormost row lacking and with a reduced number of transverse suborbital rows. Both species are isolated and their distributions restricted to a small brackish lake in the west of the Anatolian south coast. This record represents the southern and easternmost of the genus Knipowitschia in the Mediterranean region. The origin of these two species is discussed.